(untitled) (UNWE Yearbook, 2017)
The role of project portfolio management (PPM) has substantially amplified in the conditions of contemporary globalized economy. The need for the optimal resource allocation and the efficient implementation of business processes has given rise to various practices of PPM in Bulgarian project-oriented organizations. The aim of this paper is to present the findings of a recent survey, showing evidence about the extent to which the major standard PPM processes are integrated and implemented by such organizations. Using an original research instrument, data about these processes has been provided through purposive sampling of organizations that apply PPM approach in their operations. The research findings prove to be valuable to managers of project-oriented organizations as far as the processes of major importance for PPM are identified in relation to the degree of its effectiveness. Processes identified as not yet fully developed are seen a substantial source and clear potential for future improvement of PPM and enhancing its effectiveness in Bulgarian organizations.